KEY ISSUES IN ADULT NON FORMAL PARTICIPATORY E-LEARNING - Marzano, Gilberto; Lubkina, Velta; Siguencia, Luis Ochoa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This paper is concerned with participatory learning, and focuses on the issues that can arise in the application of participatory approaches in e-learning-based adult non-formal education programmes. It analyses the assumptions on which participatory learning theories lie, and discusses the current portability of participatory adult learning practices to an on-line environment. Some key issues in adult non-formal participatory e-learning will be presented, taking into account the available literature and the first results of EScAlADE, an EU funded project started at the end of 2015, which focuses on adult non-formal participatory learning.